REFLECTION OF THE PROBLEM OF IMMORTALITY IN KAZAKH MYTHOLOGY (Journal of Philosophy Culture and Political Science, 2018)
The desire for "immortality" historically comes from the very nature of the Kazakh - the nomad, surrounded by the eternal Cosmos and Nature, who, convinced of the inevitability and eternity of the world, tries to become like Him. And because this is the meaning of his life and purpose.